2016
DOI: 10.1111/pbi.12566
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic soybean overexpressing GmSAMT1 exhibits resistance to multiple‐HG types of soybean cyst nematode Heterodera glycines

Abstract: SummarySoybean (Glycine max (L.) Merr.) salicylic acid methyl transferase (GmSAMT1) catalyses the conversion of salicylic acid to methyl salicylate. Prior results showed that when GmSAMT1 was overexpressed in transgenic soybean hairy roots, resistance is conferred against soybean cyst nematode (SCN), Heterodera glycines Ichinohe. In this study, we produced transgenic soybean overexpressing GmSAMT1 and characterized their response to various SCN races. Transgenic plants conferred a significant reduction in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Similarly, in tomatoes, SAMT overexpression elevates both SA and MeSA accumulation and promotes plant disease resistance [ 24 ]. However, in soybean and Arabidopsis , SAMT overexpression causes an increase in MeSA but a drop in SA levels that leads to a weakening of disease resistance in Arabidopsis but enhances resistance in soybean [ 22 , 23 , 26 ]. These results showed that SAMT1 has different roles in the regulation of MeSA and SA -mediated disease resistance in different species or varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in tomatoes, SAMT overexpression elevates both SA and MeSA accumulation and promotes plant disease resistance [ 24 ]. However, in soybean and Arabidopsis , SAMT overexpression causes an increase in MeSA but a drop in SA levels that leads to a weakening of disease resistance in Arabidopsis but enhances resistance in soybean [ 22 , 23 , 26 ]. These results showed that SAMT1 has different roles in the regulation of MeSA and SA -mediated disease resistance in different species or varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Also, silencing the NtSAMT1 gene has been shown to block the SAR [ 19 ]. Transgenic soybeans overexpressing GmSAMT1 exhibit resistance to soybean cyst nematode [ 22 , 23 ]. SAMT overexpression in transgenic tomato plants results in delayed disease symptoms following Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%
“…Active second-stage juvenile (J2) nematodes (1000 J2 SCN/plant) were used for inoculation. SCN inoculation and bioassay for transgenic hairy root overexpressing GmAFS were performed as previously described (Lin et al, 2016). The inoculation was carried out in a growth chamber for 2 days with 16-h day length and 25°C day/night temperature.…”
Section: Scn Treatment For Breeding Lines and Scn Bioassay On Transgementioning
confidence: 99%
“…Salicylic acid is considered to be one of the key signals in plant defense mechanisms, and its relationship with plant stress resistance has been the focus of several studies. It is clear that SA can be used as a signaling molecule to induce plant disease resistance by activating the plant defense system (Lin et al, 2016; Klessig et al, 2018). It also plays important roles in tolerance to abiotic stresses, such as those induced by salt, heat, and heavy metals (Kang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%